(untitled) (Cardiovascular Journal, 2019)
Background: The characteristics of infective endocarditis (IE) have significantly changed in pediatric age group during last few decades. The present study was conducted to study the clinical & lab profile, risk factors, site of cardiac involvement and outcome of infective endocarditis in the largest children hospital of Bangladesh. Methods: This prospective cross-sectional study was conducted in cardiology department with a diagnosis of IE from February 2014 to August 2016. Twenty- four children fulfilled the modified Duke diagnostic criteria. Results: Definite IE was found in 58% (14/24) patients, while the rest had possible IE. The most common presenting symptom was prolonged fever (> 2 weeks) & heart murmur. Most commonly encountered risk factors included congenital heart disease (54%), most commonly ventricular septal defect (21%). Two patients (8.3%) had history of rheumatic heart disease. Other important risk factors include post cardiac surgery (16.7%), prolonged ICU stay of neonates (20.8%). Nineteen patients (79%) were classified as having culture-negative endocarditis and five (21%) as culture positive. The most frequently isolated organisms were streptococci and followed by staphylococci and candida. Fifteen (62.5%) patients had right-sided cardiac involvement. Seven (29%) patients died of endocarditis or its complications. Conclusion: Clinicians should have a high index of suspicion of endocarditis in persistently febrile patients with congenital heart disease and send blood cultures or refer appropriately before prescribing antibiotics. Cardiovasc. j. 2019; 12(1): 33-39